Paraoxonase 1 in neurological disorders. (March 2014) - Menini, Teresita; Gugliucci, Alejandro
Abstract : Paroxonase 1 displays multiple physiological activities that position it as a putative player in the pathogenesis of neurological disorders. Here we reviewed the literature focusing on the role of paraoxonase 1 (PON1) as a factor in the risk of stroke and the major neurodegenerative diseases. PON1 activity is reduced in stroke patients, which significantly correlates inversely with carotid and cerebral atherosclerosis. The presence of the R allele of the Q192R PON1 polymorphism seems to potentiate this risk for stroke. PON1 exerts peroxidase activities that may be important in neurodegenerative disorders associated with oxidative stress. PON1 is also a key detoxifier of organophosphates and organophosphate exposure has been linked to the development of neurological disorders in which acetylcholine plays a significant role. In Parkinson's disease most of the studies suggest no participation of either L55M or the Q192R polymorphisms in its pathogenesis. However, many studies suggest that the MM55 PON1 genotype is associated with a higher risk for Parkinson's disease in individuals exposed to organophosphates. In Alzheimer's disease most studies have failed to find any association between PON1 polymorphisms and the development of the disease. Some studies show that PON1 activity is decreased in patients with Alzheimer's disease or other dementias, suggesting a possible protective role of PON1. No links between PON1 polymorphisms or activity have been found in other neurodegenerative diseases such as multiple sclerosis and amyotrophic lateral sclerosis. PON1 is a potential player in the pathogenesis of several neurological disorders. More research is warranted to ascertain the precise pathogenic links and the prognostic value of its measurement in neurological patients.